1998
DOI: 10.1152/ajpgi.1998.275.5.g1073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neurotransmitters, gut hormones, and inflammatory mediators on mucus discharge in rat colon

Abstract: The effect of potential mediators of mucus secretion was investigated in the isolated vascularly perfused rat colon by using a sandwich enzyme-linked immunosorbent assay for rat colonic mucin and by histochemical analysis. Bethanechol (100–200 μM), bombesin (100 nM), and vasoactive intestinal peptide (VIP, 100 nM) provoked a dramatic mucin discharge (maximal response at 900, 900, and 600% of control loops, respectively). VIP-stimulated mucin secretion was abolished by tetrodotoxin, whereas atropine was without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 32 publications
5
68
0
Order By: Relevance
“…Goblet cells secrete mucin via an unregulated constitutive pathway that is dependent on the continuous movement of mucin granules from the Golgi apparatus to the apex of the cell and by a regulated process dependent on the sudden release of mucin from granules. This regulatory process is controlled by a wide variety of stimuli, including nerve activation and inflammatory mediators (6,31,33). In this study, we clearly demonstrated that leptin is one of these stimuli.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Goblet cells secrete mucin via an unregulated constitutive pathway that is dependent on the continuous movement of mucin granules from the Golgi apparatus to the apex of the cell and by a regulated process dependent on the sudden release of mucin from granules. This regulatory process is controlled by a wide variety of stimuli, including nerve activation and inflammatory mediators (6,31,33). In this study, we clearly demonstrated that leptin is one of these stimuli.…”
Section: Discussionsupporting
confidence: 53%
“…The mucin-like glycoprotein content of samples was determined from standard curves prepared from HT29-MTX mucins isolated from 75-cm 2 flasks and purified by ultracentrifugation as described previously (33). The amount of glycoprotein secreted in the incubation medium was expressed as nanograms of mucin-like glycoprotein per 10 6 cells, and results are given as percentages of controls.…”
Section: Animals Male Wistar Rats Weighing 220 -240 G (Charles Rivermentioning
confidence: 99%
“…Mucus secretagogues. Both PGE 2 and 5-HT are reported to stimulate Cl -, HCO 3 -, and mucus secretion (34)(35)(36)(37). Both agonists are endogenous to the intestine and known to be involved in both physiological functions and pathological conditions in the gut.…”
Section: Mucus Stimulationmentioning
confidence: 99%
“…A variety of peptides may also be involved in the regulation of mucus release during inflammatory states (Lamont 1992, Fairweather 1997. Plaisancié et al (1998) provided evidence that rat colonic mucin secretion may be induced by several mediators (vasoactive intestinal peptide, bombesin, and serotonin) from the neuroendocrine and immune systems, including a marked increase in the discharge of colonic mucin from the isolated vascularly perfused rat colon (Plaisancié et al 1998). Dezfuli et al (2000Dezfuli et al ( , 2002bDezfuli et al ( , 2003 showed that the presence of intestinal helminths in the intestine of the brown trout induced alterations in the occurrence and distribution of the components belonging to the host neuroendocrine system.…”
Section: Discussionmentioning
confidence: 99%